Endoscopic ultrasound-guided liver biopsy in pediatric patients - Johal, Amitpal S. (Medknow Publications & Media Pvt Ltd, 2014)
Endoscopic ultrasound (EUS) is routinely used for diagnostic and therapeutic purposes in adults, and there is emerging literature on its feasibility and safety in children. A recent novel application is EUS-guided liver biopsy (EUS-LB), which has shown to be technically simple, safe, and provides adequate diagnostic yield in adults for evaluation of liver disease; but the use of EUS-LB has never been evaluated in the pediatric population. We report the first case series of EUS-LB in the pediatric population, performed on 3 children, 1 girl and 2 boys-ages 9, 14 and 17 respectively, using a 19-gauge EUS-fine needle aspiration needle. All three cases were performed for the evaluation of unexplained elevated liver enzymes, with above-average diagnostic yield and without any immediate or delayed complications in all children. The use of EUS-LB was pivotal in the management of all the cases. Our case series illustrates the diagnostic utility and safety of EUS-LB in pediatric patients.